Pvt Correlation for Libyan Crude Oils - Derdar, Mawaheb M. Zarok; Almeshergi, Asia A. (جامعة طرابلس - نقابة أعضاء هيئة التدريس, 2015)
The aim of this study is developing a correlation for gas/oil ratio as function gas oil gravity, gas gravity, bubble point pressure, and reservoir bottom hole temperature which can applicable for Libyan crude oils. The PVT data were collected from different Libyan oil fields, and new correlation was based on 81 different crude oil fields. A multiple regression analysis technique was utilized for this study to create a reasonable model that could predicate the different fluid properties. A lot of sensitivity analyses were performed in order to check the parameters sensitivity to build a proper mathematical expression for PVT fluid properties. This study has produced a useful correlation which could be used for Libyan oil field. However, this correlation found to be the best for the Libyan oil compared with six other published correlations.
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- النمو الإقتصادي -- الموارد البشرية -- الثروات القومية -- النفط -- مستخلصات الأبحاث